Some 1,2,3-trisubstituted cyclopentanes. - Grewal, Gurherdial Singh. (University of Ottawa (Canada), 1961)
This thesis is concerned with the preparation of five membered ring compounds. Some 1,2,3-trisubstituted cyclopenetanes were prepared in order to get information related to conformational analysis in the reactions of centres in five membered ring compounds. 3-Acetoxycyclopentene and 3-methoxycyclopentene were used as starting materials for the preparation of these compounds. Treatment of 3-acetoxyxyclopentene and 3-methoxycyclopentene with perbenzoic acid gave the corresponding trans-oxides. The structure of these oxides were determined by chemical means. 1,2,3-Cyclopentanetriols obtained by way of wet and dry Prevost reactions of 3-acetoxycyclopentene and from the hydrolysis of trans-oxide of 3-acetoxycyclopentene were separated by partition chromatography using Celite to hold the static aqueous phase and n-butanol equilibrated with five percent boric acid solution as solvent system. Structures of 1alpha,2alpha,3beta and 1alpha,2beta,3alpha cyclopentanetriols were proved by chemical means and some solid derivatives of these compounds were prepared. The proton resonance spectra of 1alpha,3alpha-dimethoxy-2beta-acetoxycyclopentane and 1alpha-p-nitrobenzoate-2beta-bromo-3alpha-acetoxycyclopentane were taken. The reactions of above mentioned substances and other related five membered ring compounds are reported in the theses.
Keywords: Chemistry, Organic.